A nodulin/glutamine synthetase-like fusion protein is implicated in the regulation of root morphogenesis and in signalling triggered by flagellin - Doskočilová, Anna; Plíhal, Ondřej; Volc, Jindřich; Chumová, Jana; Kourová, Hana; Halada, Petr; Petrovská, Beáta; Binarová, Pavla (Planta, 2011)
The nodulin/glutamine synthetase-like protein (NodGS) that we identified proteomically in Arabidopsis thaliana is a fusion protein composed of an N-terminal amidohydrolase domain that shares homology with nodulins and a C-terminal domain of prokaryotic glutamine synthetase type I. The protein is homologous to the FluG protein, a morphogenetic factor in fungi. Although genes encoding NodGS homologues are present in many plant genomes, their products have not yet been characterized. The Arabidopsis NodGS was present in an oligomeric form of ~700-kDa, mainly in the cytosol, and to a lesser extent in the microsomal membrane fraction. The oligomeric NodGS was incorporated into large heterogeneous protein complexes >700 kDa and partially co-immunoprecipitated with γ-tubulin. In situ and in vivo microscopic analyses revealed a NodGS signal in the cytoplasm, with endomembranes, particularly in the perinuclear area. NodGS had no detectable glutamine synthetase activity. Downregulation of NodGS by RNAi resulted in plants with a short main root, reduced meristematic activity and disrupted development of the root cap. Y2H analysis and publicly available microarray data indicated a role for NodGS in biotic stress signalling. We found that flagellin enhanced the expression of the NodGS protein, which was then preferentially localized in the nuclear periphery. Our results point to a role for NodGS in root morphogenesis and microbial elicitation. These data might help in understanding the family of NodGS/FluG-like fusion genes that are widespread in prokaryotes, fungi and plants.
Keywords: membránové proteiny; signální transdukce; Genes, Plant; Gene Expression Regulation, Plant; Membrane Proteins; flagelin; rostlinné geny; Signal Transduction; Arabidopsis Proteins; regulátory růstu rostlin; Plant Roots; Flagellin; Morphogenesis; proteiny huseníčku; rostlinné proteiny; kořeny rostlin; Plant Proteins; regulace genové exprese u rostlin; morfogeneze; Plant Growth Regulators; Glutamate-Ammonia Ligase; glutaminsynthetasa; Arabidopsis